Evaluation of the Tourism Management System from a Social, Economic and Environmental Perspective in Suka Makmur Village, Deli Serdang Regency - Lubis, Muhammad Rizki; Lingga, Osland Herijon; Khadry, Muhammad; Ramadhan, Ikhlas (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to evaluate the tourism management system in Suka Makmur Village, Deli Serdang Regency, from three main perspectives: social, economic, and environmental.. Research methods: The research was conducted in Suka Makmur Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The research employed a descriptive method with a qualitative approach through interviews, participatory observation, documentation, and questionnaires administered to tourists and local residents. Results and discussion: The findings indicate that, from an economic perspective, tourism management has positively contributed by increasing income, creating jobs, and fostering micro-business growth, although product diversification and promotional effectiveness still require improvement. From a social perspective, community participation is relatively high in operational management and communal activities, yet the involvement of youth and enhancement of managerial capacity remain necessary. Environmentally, some ecotourism principles have been implemented, including nature conservation and cleanliness efforts, though waste management and environmental education need strengthening. The SWOT analysis identified weaknesses such as limited infrastructure and promotion, challenges including fluctuating visitor numbers and environmental degradation risks, and opportunities in developing culture-, nature-, and culinary-based products. Implication: Recommendations include enhancing digital promotion strategies, diversifying tourism products, strengthening community roles, and fully integrating ecotourism principles